Rural water for thirsty cities: a systematic review of water reallocation from rural to urban regions - Garrick, D.; Stefano, L. de; Yu, Winston; Jorgensen, I.; O’Donnell, E.; Turley, L.; Aguilar-Barajas, I.; Dai, X.; Souza Leao, R. de; Punjabi, B.; Schreiner, B.; Svensson, J.; et al. (IOP Publishing, 2019)
Background: Competition for freshwater between cities and agriculture is projected to grow due to rapid urbanization, particularly in the Global South. Water reallocation from rural to urban regions has become a common strategy to meet freshwater needs in growing cities. Conceptual issues and associated measurement problems have impeded efforts to compare and learn from global experiences. This review examines the status and trends of water reallocation from rural to urban regions based on academic literature and policy documents. Methods: We conduct a systematic literature review to establish the global reallocation database (GRaD). This process yielded 97 published studies (academic and policy) on rural-to-urban reallocation. We introduce the concept of reallocation ‘dyads’ as the unit of analysis to describe the pair of a recipient (urban) and donor (rural) region. A coding framework was developed iteratively to classify the drivers, processes and outcomes of water reallocation from a political economy perspective. Results: The systematic review identified 69 urban agglomerations receiving water through 103 reallocation projects (dyads). Together these reallocation dyads involve approximately 16 billion m3 of water per year moving almost 13 000 kilometres to urban recipient regions with an estimated 2015 population of 383 million. Documented water reallocation dyads are concentrated in North America and Asia with the latter constituting the majority of dyads implemented since 2000. Synthesis: The analysis illustrates how supply and demand interact to drive water reallocation projects, which can take many forms, although collective negotiation and administrative decisions are most prevalent. Yet it also reveals potential biases and gaps in coverage for parts of the Global South (particularly in South America and Africa), where reallocation (a) can involve informal processes that are difficult to track and (b) receives limited coverage by the English-language literature covered by the review. Data regarding the impacts on the donor region and compensation are also limited, constraining evidence to assess whether a water reallocation project is truly effective, equitable and sustainable. We identify frameworks and metrics for assessing reallocation projects and navigating the associated trade-offs by drawing on the concept of benefit sharing.